(untitled) (Journal of the College of Basic Education, 2022)
The purpose of the research is to find out the evaluation of the administrative efficiency of the members of the committees supervising the teaching applications in the faculties of education at the University of Baghdad from the point of view of the supervisors. The research adopted descriptive analytical method. The research community consisted of (162) supervisors of teaching applications from faculties of education / University of Baghdad. The sample of the research was chosen in a simple random way. The sample number (120) supervisors from the above mentioned colleges. A questionnaire consisting of (35) items was distributed among the four fields of research. The researchers confirmed their sincerity and persistence. The research data were analyzed using the SPSS program, and the questionnaire was applied in the first semester of 2017/2018. The researchers found the most important results: The field of guidance ranked first among the four areas of great importance in enabling the applied students to perform their teaching and benefit from the guidance.